Analisis Penilaian Financial Distress Menggunakan Model Altman (Z-Score) Pada PT Gudang Garam Tbk Periode 2015 - 2024 - Maulidia Fitriana; Lina Nofiana (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
This study aims to predict the bankruptcy risk of PT Gudang Garam Tbk during the period 2015 to 2024 using the Altman Z-Score method. The Altman Z-Score is one way to estimate whether a company has the potential to go bankrupt. This research is a quantitative research type with a descriptive approach. This study analyzes five main variables, namely the ratio of Working Capital to Total Assets (X1), Retained Earnings to Total Assets (X2), EBIT to Total Assets (X3), Market Value of Equity to Total Liabilities (X4), and Sales to Total Assets (X5). All data used comes from the annual financial statements of PT Gudang Garam Tbk and is calculated using the Altman Z-Score formula to evaluate the company's financial condition. The results of the study show that the Z-Score value of PT Gudang Garam Tbk for the past ten years is in the range of 1.1257 to 1.4921. All of these values are lower than the minimum threshold of 1.81, thus placing the company in the bankruptcy zone category respectively